Three-dimensional interaction between Cinnamomum camphora and a sap-sucking psyllid insect (Trioza camphorae) revealed by nano-resolution volume electron microscopy - Guan Wang; Jian-Sheng Guo; Hai-Jian Huang; Zeng-Rong Zhu; Chuan-Xi Zhang (Communications Biology)
Abstract Phloem-feeding insects present significant economic threats worldwide and remain challenging to understand due to their specialized feeding strategies. Significant advances in genetics, genomics, and biochemistry have greatly enriched our comprehension of phloem–insect interactions. However, existing studies relying on two-dimensional discrete images have limited our understanding of visible morphological details. In this study, we leverage volume electron microscopy (vEM) technology to unveil a nanometer-resolution interaction mode between plant and the phloem-feeding insect, Camphor psyllid (Trioza camphorae, Hemiptera: Psyllidae). The stylets penetrate each cell on the way to the feeding site (sieve tube), and new cell walls will form around the salivary sheath, ultimately fusing with the original cell walls to form remarkably thickening cell walls. Our reconstruction findings on pit gall tissues suggest that a significant decrease in cell volume and a drastic increase in cell layers are the primary processes during pit gall formation. These unique findings will set the stage for a robust discussion on the plant cellular response induced by phloem-feeding insects.